Atravessando a ponte, vivendo na linha: marcos e marcas de uma cultura de fronteira à luz da fotoetnografia - Rebelatto, Francieli (2011)
This paper proposes using the complementarity of text and writing an ethnographic photoethnographic do some reading about the displacement of the subjects in the urban towns of Uruguaiana (BRA) and Paso de los Libres (ARG), Deliverance (BRA) and Rivera (URU). When people move on space planning, move with them cultural and material goods, ways of thinking and seeing the world. These guys crossing the bridge or take the line with them all their references to the world allowing that culture can be seen as a make, which can be produced and reproduced. In these various shifts for a diversity of views on the border, so try to understand how individuals who live in or are just passing through it, move in this space, how they relate from territorial marks, discussing the concepts of anthropological place and no place proposed by Marc Augé (1994). To present and describe the seizures made from the resort to fieldwork as photoethnographic founding of this research methodology, and this study included in discussions of audiovisual anthropology.